Imagem e imaginário dos vilões contemporâneos: o vilão como representação do mal nos quadrinhos, cinema e games - Faria, Mônica Lima de (2012)
This study presents the villains of comic books, movies and games in contemporary visual media through a focus on your images and imagined in modernity, and especially in post-modernity. In the study, selected images of these villains are understood elements of media and visual communication, which are relevant in the postmodern condition. Are first studied the concepts of communication and imaginary and their relationships, followed by a contextualization of comic books, movies and games in order to realize the theoretical framework suggested for research. Then questions will be presented on the picture and then focusing on imaginary of modernity and the postmodern condition, emphasizing their contextualization and characteristics with regard to communication, image and imaginary. On another occasion, it is discussed the figure of the villain, his image and imaginary in which the characters are seen as a representation of evil, starting with a discussion of ethics as a way to understand evil, through notions of evil pointed out by Ricoeur (2007) and Maffesoli (2004) and noting, finally, the theoretical framework as the villain character who is evil, its visual manifestations and imaginary. The present study also analyzes two villains - one of modern features and other features of post-modern - as well as an anti-hero, as follows: Saruman, the film trilogy The Lord of the Rings; Joker, from the graphic novel Arkham Asylum - a serious home in a serious world, and Ezio of Assassin's Creed II game. The analyzes are carried out in three stages, namely: presentation of the character - that contextualizes the object -; imaginary and evil´s moral - that discusses the villain analyzed in relation to the theoretical frameworks presented on the imaginary and evil -, and imaginary and image of evil - when they are presented the relations of visual manifestations of the characters and the construction of his imagination as a representation of evil. After a discussion is made on the results of the analyzes. The study then makes the case that the image and the imaginary villain's contemporary - of comic books, movies and games - no more respect the dualities of good and evil set up to modern times. This new postmodern villain, through its images, however evil, shows through your images and imaginary a relativization of evil, which is a complement to the right, visible in the construction of contemporary anti-hero. Thus, the study is a qualitative research which is used as a methodological approach Depth Hermeneutics by J. Thompson (1995), this approach also permeates the technique of content analysis proposed by Bardin (1977).